Blowhole Colostomy for Clostridium difficile-Associated Toxic Megacolon - Jeroen Kerstens; Ian Diebels; Charles de Gheldere; Patrick Vanclooster (Case Reports in Surgery)
We present the case of a 58-year-old man who underwent urgent blowhole colostomy for toxic megacolon (TM) secondary to Clostridium difficile infection (CDI). This infection occurred under antibiotic coverage with amoxicillin-clavulanic acid, four days after laparoscopic sigmoidectomy in our hospital. Although prospective clinical research regarding the surgical management of TM is lacking, decompressive procedures like blowhole colostomy are reported to carry a high risk of postoperative morbidity and mortality and are widely regarded as obsolete. Subtotal or total colectomy with end ileostomy is currently considered the procedure of choice. After presenting our case, we discuss the literature available on the subject to argue that the scarce evidence on the optimal surgical treatment for TM is primarily based on TM associated with inflammatory bowel diseases (IBD) and that there might be a rationale for considering minimally invasive procedures like blowhole colostomy for CDI-associated TM.